Effects of Green Beans (Phaseolus vulgaris L.) Extracts on Triglyceride Levels of Wistar Rats with Hyperlipidemia - Khairunnisa Nurul Huda; Andri Putranto; Muthmainah . (Fakultas Kedokteran Universitas Sebelas Maret Surakarta, 2016)
Introduction: Dyslipidemia is characterized by increase of triglyceride. This lipid disorder associates with obesity, stroke and heart diseases. A recent study has been reported that the use of triglyceride-lowering drugs have many side effects. Therefore, some patients of dyslipidemia prefer to use complementer medicine like herbal medicine rather than the existing drugs. Green bean contains some secondary metabolites, which have hypolipidemic effects. This present study aimed to investigate the effect of green bean (Phaseolus vulgaris L.) extract on triglyceride levels of rats with hyperlipidemia. Methods: This study was a laboratory experimental study with post test only control group design. Male Wistar rats, which aged 3 months old, and weighted 200 g were use in this study. Thirty rats were divided into five groups : two control groups (KKn, KKi) and 3 treatment groups. KKn was given distilled water and KKi was given 4.5 mL duck egg yolks orally and propylthiouracil (PTU) 0.01% ad libitum for 28 days. The treatment groups were given the same diet as the KKi group for 28 days. Green bean extract (GBE) (50, 100, and 150 mg/200g; per oral) was added in three treatment groups by the fifteen days of the experiment. The following day, rats were sacrificed and blood was collected from rats plexus retro-orbital. The serum triglyceride levels were determined using spectrophotometer. All collected data were analyzed by using One Way ANOVA test followed by Post Hoc test (? = 0.05). Result: Triglyceride levels of rats treated with green bean extracts (KP1, KP2, KP3) were lower than the control groups (KKn, KKi). The difference of triglyceride level reached significantly p = 0.000. The first treatment (KP1) group has 46.83 20.62 mg/dL triglyceride level, which was higher than other treatment group (KP2, KP3) (30 9.65 and 40.17 11.37 mg/dL). However, it was not statistical difference. Conclusions: Green Bean (Phaseolus vulgaris L.) extract 50-150 mg/bodyweight can reduce triglyceride levels of Wistar rats with hyperlipidemia. Further investigation will be required for determination of the effective dose reducing triglyceride level in the animal model. Keywords: green bean, triglyceride, hyperlipidemia, Rattus norvegicus